Changes in milk fat globules and membrane lipids under the shear fields of microfiltration and centrifugation - Jukkola, Annamari; Hokkanen, Sanna; Kämäräinen, Tero; Partanen, Riitta; Heino, Antti; Rojas, Orlando J. (Journal of Membrane Science, 2019)
This study compared the efficiency of centrifugal and microfiltration separation of milk fat globules (MFG) from bovine cream and the changes that take place in the corresponding lipid membranes (MFGM). Creams were washed with water (1:10) and subjected to either centrifugation or microfiltration to fractionate proteins and other non-fat milk components. Protein analyses of the obtained fractions were carried out by gel electrophoresis. Lipid extraction and thin layer chromatography were also employed to separate lipid types and the amount of polar lipids were determined by gas chromatography. The effect of flow conditions on MFG's colloidal properties and MFGM components was evaluated based on estimates of the average rate of energy dissipation in microfiltration and centrifugation processes. Both were equally effective in removing the protein fraction (93% yield) as well as non-fat dry matter ( 100% removal). Microfiltration reduced the mean particle size by 0.3 µm, whereas the opposite was observed for centrifugal separation (average size increase by 0.8 µm). The latter process also induced a more significant reduction in the electrostatic charges (zeta potential) of the colloids in the cream, which relates to the changes in the milk fat globule surface composition and the release of MFGM components. The dissociated polar lipids amounted to 24% and 20% upon centrifugation and microfiltration, respectively. Overall, the results suggest that MFG and MFGM are partially damaged under the shear forces typical of centrifugal and microfiltration separation. A high separation efficiency, with minimal fat globule damage and high MFGM yield is possible by adopting microfiltration under carefully optimized conditions.
Created from Fastlane, Scopus look-up
Keywords: Centrifugation; Microfiltration; Milk fat globule membrane (MFGM); Milk fat globules; Shear